Adapting the Brief COPE for Chinese Adolescents with Visual Impairments. (January 2017) - Yuan, Wei; Zhang, Li-fang; Li, Bing
Introduction: The present research pioneered the effort in assessing adolescents' coping with visual impairment through adapting the Brief COPE in an eastern context. The first study preliminarily explored the applicability of the Brief COPE to Chinese adolescent students with visual impairments. Based on the results, the Brief COPE was modified and renamed, COPE-Revised. The second study tested the internal psychometric properties and the criterion-related validity of the COPE-Revised. Criterion-related validity was obtained through investigating the correlation between coping and self-esteem. Method: The first study involved 176 adolescent students with visual impairments, comprising a survey using the Brief COPE and follow-up interviews. In the second study, another cohort of 170 adolescent students with visual impairments responded to the COPE-Revised together with an inventory assessing self-esteem. Results: The COPE-Revised showed adequate psychometric properties. Three higher-order factors, namely self-directed, other-directed, and relinquished-control coping, were identified. The way in which self-esteem was correlated with these three dimensions of coping provided evidence for the criterion-related validity of the COPE-Revised. Discussion: The findings indicate that the COPE-Revised has sound psychometric properties among adolescents with visual impairments. Limitations regarding the sample-selection bias and the means of questionnaire survey among visually impaired adolescents are noted. Implications for practitioners: This research tailored a coping inventory for educators, counselors, and researchers who are interested in investigating adolescents' ability to cope with visual impairments. The relationship between coping with visual impairment and self-esteem found in this research has reference significance for educational and counseling services for visually impaired adolescents.